2021
DOI: 10.1098/rsos.202099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on the simultaneous anammox and denitrification process: performance, sludge morphology and shifts in microbial communities

Abstract: In this study, the long-term effects of different salinities on the performance, sludge morphology and shifts in microbial communities were studied in a simultaneous anammox and denitrification (SAD) process at a C/N ratio of 0.5. Stable nitrogen removal efficiencies of 86.96 and 84.58% and nitrogen removal rates of 0.95 and 0.93 kg (m 3 d) −1 could be achieved under low (25 mmol l −1 ) and moderate (50 mmol l −1 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The process combined with anaerobic or aerobic treatments (activated sludge and partial nitritation) ahead has been applied for saline wastewater from industrial manufacturing, such as fish canning and mustard pickling . The anammox process can acclimatize to saline conditions but is considered inefficient for high-salinity (>10–18 g NaCl/L) wastewater because of its decreased microbial activity and poor sludge granulation. Water reclamation is commonly implemented during freshwater shortages and for sustainable development initiatives and leads to increases in wastewater salinity. Domestic wastewater can be salinized because seawater is sometimes used for flushing toilets in water-scarce areas .…”
Section: Introductionmentioning
confidence: 99%
“…The process combined with anaerobic or aerobic treatments (activated sludge and partial nitritation) ahead has been applied for saline wastewater from industrial manufacturing, such as fish canning and mustard pickling . The anammox process can acclimatize to saline conditions but is considered inefficient for high-salinity (>10–18 g NaCl/L) wastewater because of its decreased microbial activity and poor sludge granulation. Water reclamation is commonly implemented during freshwater shortages and for sustainable development initiatives and leads to increases in wastewater salinity. Domestic wastewater can be salinized because seawater is sometimes used for flushing toilets in water-scarce areas .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that the majority of heterotrophic bacteria capable of organic matter degradation belong to Proteobacteria [39], and several types of denitrification bacteria have also been classified within this phylum [40]. The relative abundance of Proteobacteria in R40 even reached 90.96%, potentially attributed to the proliferation of halophilic heterotrophic bacteria induced by salinity [41]. Simultaneously, the consistent presence of Bacteroidota across all samples ensured efficient nitrogen removal under saline conditions, as it has been proved to have high capability for the oxidation of ammonium [37] and is associated with salt-tolerant denitrifying bacteria [41].…”
Section: Effect On Microbial Community Structurementioning
confidence: 80%
“…The relative abundance of Proteobacteria in R40 even reached 90.96%, potentially attributed to the proliferation of halophilic heterotrophic bacteria induced by salinity [41]. Simultaneously, the consistent presence of Bacteroidota across all samples ensured efficient nitrogen removal under saline conditions, as it has been proved to have high capability for the oxidation of ammonium [37] and is associated with salt-tolerant denitrifying bacteria [41]. In addition, Proteobacteria tended to secrete EPS in unfavorable environments that promoted granulation [42].…”
Section: Effect On Microbial Community Structurementioning
confidence: 95%
“…Wang et al [32] found that salinity had a greater impact on EPS content than on EPS composition, and Liu and Tay [33] further revealed that high EPS content was conducive to sediment formation and biofilm stability. Lay et al [32] also found that EPS had high adsorption properties and affinity for cations, thereby forming an adsorption layer on the surface of the membrane, which changed the interface electrochemical potential and further affected the mass transfer of salts in the biofilm. Under S1 conditions, two peaks at 1390 cm −1 and 1229 −1 were scanned; the corresponding functional groups were carboxyl or hydroxyl compounds C-H, CH 2 -, and protein-related amide III regions, respectively.…”
Section: Ftir Analysismentioning
confidence: 99%
“…Studies have shown that the EPS content of biofilms is affected by environmental factors and operating conditions, and its compositional characteristics are mainly dependent on the wastewater matrix [31]. Wang et al [32] found that salinity had a greater impact on EPS content than on EPS composition, and Liu and Tay [33] further revealed that high EPS content was conducive to sediment formation and biofilm stability. Lay et al [32] also found that EPS had high adsorption properties and affinity for cations, thereby forming an adsorption layer on the surface of the membrane, which changed the interface electrochemical potential and further affected the mass transfer of salts in the biofilm.…”
Section: Ftir Analysismentioning
confidence: 99%